PEMBERANTASAN KORUPSI DAN PERWUJUDAN INTEGRITAS PUBLIK DALAM PERSPEKTIF MUHAMMADIYAH DAN NU - Biyanto, Biyanto (JURNAL PENELITIAN KEISLAMAN, 2010)
This article aims spesifically to discuss the experiences of Muhammadiyah and NU in eradicating corruption and upholding public integrity. This topic is important because Muhammadiyah and NU showed serious effort of eradicating corruption and upholding public integrity. According to Muhammadiyah and NU, corruption could clearly harm the state economy, reduce public welfare, destroy social morality, demolish political and legal systems, threat national defense, and hammer natural resources. Indeed, Muhammadiyah and NU never explicitly use the term âanti-corruptionâ. However, viewed from the substance of their acitivities, they do engage in eradicating corruption. Muhammadiyah and NU seek to uphold public integrity, such as the advocating of transparent state budget use. These two Muslim organizations agenda in this project include encouraging public awareness of the budge planning and composition and its implemention. Interestingly, Muhammadiyah and NU also use mass media to promote their agenda of upholding public integrity. It can be observed throught the publication of activities and accountability reports published in Matan and Suara Muhammadiyah, two magazines affiliated with Muhammadiyah, and Aula, NU community monthly journal. In addition, they also collaborate with other media, such as newspaper and private radio and television to build up a culture of public integrity.